Adaptation of anaerobic cultures of Escherichia coli K‐12 in response to environmental trimethylamine‐N‐oxide. (3rd February 2015) - Denby, Katie J.; Rolfe, Matthew D.; Crick, Ellen; Sanguinetti, Guido; Poole, Robert K.; Green, Jeffrey
Summary Systematic analyses of transcriptional and metabolic changes occurring when Escherichia coli K‐12 switches from fermentative growth to anaerobic respiratory growth with trimethylamine‐N‐oxide (TMAO) as the terminal electron acceptor revealed: (i) the induction of torCAD, but not genes encoding alternative TMAO reductases; (ii) transient expression of frmRAB, encoding formaldehyde dehydrogenase; and (iii) downregulation of copper resistance genes. Simultaneous inference of 167 transcription factor (TF) activities implied that transcriptional re‐programming was mediated by 20 TFs, including the transient inactivation of the two‐component system ArcBA; a prediction validated by direct measurement of phosphorylated ArcA. Induction of frmRAB, detection of dimethylamine in culture medium and formaldehyde production when cell‐free extracts were incubated with TMAO suggested the presence of TMAO demethylase activity. Accordingly, the viability of an frmRAB mutant was compromised upon exposure to TMAO. Downregulation of genes involved in copper resistance could be accounted for by TMAO inhibition of Cu(II) reduction. The simplest interpretation of the data is that during adaptation to the presence of environmental TMAO, anaerobic fermentative cultures of E. coli respond by activating the TorTSR regulatory system with consequent induction of TMAO reductase activity, resulting in net oxidation of menaquinone and inhibition of Cu(II) reduction, responses that are sensed by ArcBA and CusRS respectively.